Evaluasi Aksesibilitas Website Akademik bagi Pengguna Disabilitas Menggunakan Website Accessibility Conformance Evaluation Methodology (WCAG-EM) - Aryantoputri, Biandra; Suranto, Beni (AI Society & STMIK Indonesia, 2025)
This study evaluates the accessibility of the academic website of Universitas Islam Indonesia (UII) using AChecker and WAVE tools based on the Web Content Accessibility Guidelines (WCAG) standards. The results indicate that most pages have potential accessibility issues, such as